A Study of Subtitle Translation Strategies Used to Translate the Offensive Language in Billions - Niko Hernando (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study examines the expressions considered as offensive language produced by all characters in their workplaces in Billions and the subtitle translation strategies used to translate them. The writer applied two theories: Battistella’s (2005) theory of offensive language and Pedersen’s (2011) theory of subtitle translation strategy. This study was done using a qualitative approach. The expressions produced fall into all four categories: Vulgarity, Epithets, Profanity, and Obscenity. In addition, four out of six subtitle translation strategies are used to translate the offensive language: Substitution, Omission, Generalization, and Direct Translation. Both Retention and Specification are not used. Some expressions that are linguistically considered offensive language may not carry the offense when applied in a certain context of the conversation. Substituting the offensive language with another local expression ensures the message is delivered and maintains the unpleasant impression whereas euphemizing or eliminating it may significantly alter the original nuance.